Decoding the Future of Finance: An Examination of Asset Tokenization and Web 3.0 - Shi, Jianzheng (Eximia, 2023)
This paper explores the rapidly evolving landscape of asset tokenization within the broader context of Web 3.0. Asset tokenization, the process of converting rights to an asset into a digital token on a blockchain, presents a transformative opportunity for various sectors, especially finance. This paper delves into the technicalities of asset tokenization, discusses its potential impacts, and forecasts its role in the future of digital economies. It argues that asset tokenization, fueled by the advancements in Web 3.0, will play a pivotal role in the democratization of finance, reducing entry barriers, and creating more efficient and transparent systems.